Review on the Role of Epigenetic Modifications in Doxorubicin-Induced Cardiotoxicity - Kumari, Himani; Huang, Wan-Hong; Chan, Michael W. Y. (Frontiers in Cardiovascular Medicine, 2020)
Use of anthracyclines such as doxorubicin (DOX), for the treatment of cancer, is known to induce cardiotoxicity, begetting numerous evaluations of this adverse effect. This review emphasizes the mechanism of how consideration of DOX-induced cardiotoxicity is important for the development of cardioprotective agents. As DOX is involved in mitochondrial dysfunction, enzymes involved in epigenetic modifications that use mitochondrial metabolite as substrate are most likely to be affected. Therefore, this review article focuses on the fact that epigenetic modifications, namely, DNA methylation, histone modifications, and noncoding RNA expression, contribute to DOX-associated cardiotoxicity. Early interventions needed for patients undergoing chemotherapy, to treat or prevent heart failure, would, overall, improve the survival, and quality of life of cancer patients. These epigenetic modifications can either be used as molecular markers for cancer prognosis or represent molecular targets to attenuate DOX-induced cardiotoxicity in cancer patients.